Multi‐compartmental diffusion characterization of the human cervical spinal cord in vivo using the spherical mean technique. (1st February 2018) - By, Samantha; Xu, Junzhong; Box, Bailey A.; Bagnato, Francesca R.; Smith, Seth A.
Abstract : The purpose of this work was to evaluate the feasibility and reproducibility of the spherical mean technique (SMT), a multi‐compartmental diffusion model, in the spinal cord of healthy controls, and to assess its ability to improve spinal cord characterization in multiple sclerosis (MS) patients at 3 T. SMT was applied in the cervical spinal cord of eight controls and six relapsing‐remitting MS patients. SMT provides an elegant framework to model the apparent axonal volume fraction v ax, intrinsic diffusivity D ax, and extra‐axonal transverse diffusivity D ex_perp (which is estimated as a function of v ax and D ax ) without confounds related to complex fiber orientation distribution that reside in diffusion MRI modeling. SMT's reproducibility was assessed with two different scans within a month, and SMT‐derived indices in healthy and MS cohorts were compared. The influence of acquisition scheme on SMT was also evaluated. SMT's v ax, D ax, and D ex_perp measurements all showed high reproducibility. A decrease in v ax was observed at the site of lesions and normal appearing white matter ( p < 0.05), and trends towards a decreased D ax and increased D ex_perp were seen. Importantly, a twofold reduction in acquisition yielded similarly high accuracy with SMT. SMT provides a fast, reproducible, and accurate method to improve characterization of the cervical spinal cord, and may have clinical potential for MS patients. Abstract : The spherical mean technique, a multi‐compartmental diffusion model, provides measures of axonal volume fractions ( v ax ), intrinsic diffusivity ( D ax ), and transverse extra‐axonal diffusivity ( D ex_perp ). All measurements yield high reproducibility in the spinal cord of healthy controls. In the spinal cord of patients with multiple sclerosis (MS), a decreased v ax, decreased D ax, and increased D ex_perp are observed. Furthermore, SMT is robust despite significant decreases in scan time, capable of providing accurate estimation of tissue parameters in half the scan time.